Vocal Education in Kazan: From Amateur Music Playing to Professional Training - Aleksandrovna Martynova, Yulia (2021)
The article is devoted to vocal education in Kazan as part of a general cultural process. Kazan as “a gathering place of two worlds – the Western and the Eastern”, was the leading music and cultural center. This city was simultaneously one of the largest provincial centers of Russian culture, and Muslim Tatar’s. During the XIX century in Kazan not only amateur music-making was actively developed but also were created music-public associations and private music teachers became widespread. The concert and performance in Kazan inevitably went through single phases and stages of development common to the whole country. Over time, amateur performance gives way to professional performance. The article is used a set of humanitarian and historical methods. The materials may be interesting for researchers of music education in Russia, as well as Russian provincial culture.